The Politics of Financial Development - The Role of Interest Groups and Government Capabilities - Oscar Becerra; Eduardo Cavallo; Carlos Scartascini (Inter-American Development Bank (IDB), 2010)
Although financial development is good for long-term growth, not all countries pursue policies that render full financial development. This paper builds on an extensive political economy literature to construct a theoretical model showing that the intensity of opposition to financial development by incumbents depends on both their degree of credit dependency and the role of governments in credit markets. Empirical evidence for this claim is provided, and the results suggest that lower opposition to financial development leads to an effective increase in credit markets development only in those countries that have high government capabilities. Moreover, improvements in government capabilities have a significant impact on credit market development only in those countries where credit dependency is high (thus, opposition is low). This paper therefore contributes to this rich literature by providing a unified account of credit market development that includes two of its main determinants, traditionally considered in isolation.
Keywords: G10; G18; G20; G38; O16; D72; 330; Financial development; Interest groups; Political economy; Government capabilities